Reference Values of the Central Corneal Thickness with Different Refractive Errors for the Adult Egyptian Population - Gab-Alla AA (Dove Medical Press, 2020)
Amr A Gab-Alla Suez Canal University, Faculty of Medicine, Ophthalmology Department, Ismailia, EgyptCorrespondence: Amr A Gab-AllaSuez Canal University, Faculty of Medicine, Ophthalmology Department, Ring Road, Ismailia, EgyptTel +201222836261Email amrophth@hotmail.comAim: To generate reference values of the central corneal thickness (CCT) with different refractive errors for the adult eastern Egyptian population.Subjects and Methods: This study was a retrospective, observational, and cross-sectional study. It included 1166 eyes (1166 subjects) scheduled for LASIK, who came to private refractive eye centre, Ismailia, Egypt. The study period was from January 2018 to January 2020. The subjects were divided into a broad range of myopia with spherical equivalent (SE) ≤-0.5D and hyperopia (SE) ≥+0.5D. Then, the myopic eyes divided into low (SE>-3.0D), moderate (SE-3.0D to >-6.0D), and high (SE≤-6.0D). Similarly, the hyperopic eyes were divided into low (SE<+3.0D) and moderate (SE+3.0D to <+6.0D) and high ≥+6.0D. The refractive error was measured by an auto-refractometer, and CCT was measured using ultrasonic pachymetry.Results: The data of 556 myopic eyes in 556 subjects (31.1% males and 68.9% females) and 610 hyperopic subjects (34.4% males and 65.6% females) were included in this study. The mean±SD of CCT for the total myopic subjects was 532.8± 32.6μm, range (470 to 627μm). The mean±SD of SE was -4.06± 2.50D, range (− 0.50 to − 14.00D). The mean±SD of CCT for the total hyperopic subjects was 530.8± 37.2μm, range (471 to 616μm). The mean±SD of SE was +3.57± 1.98D, range (+0.50 to +8.50D). About 16.2% of the myopic eyes and 12.7% of the hyperopic eyes have CCT less than 500μm.Conclusion: The mean of the central corneal thickness of the eastern Egyptian population was 532.8μm for myopic and 530.8μm for hyperopic subjects, respectively. The myopic and hyperopic subjects show a reduction in CCT with age. Females have a thinner cornea than males, 16.2% of the myopic eyes and 12.7% of the hyperopic eyes have CCT less than 500μm.Keywords: central corneal thickness, myopia, hyperopia, refractive errors